A Comparative Systematic Review of KTSP, K13, and Merdeka Curricula in Developing Arabic Language Competence at The Middle School Level - Khaerul Muttakin; Azzyra Sholikhatun Nisa; Ilham Dhyaul Wahid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to examine the relative effectiveness and contextual advantages of the Education Unit Level Curriculum (KTSP), the 2013 Curriculum (K13), and the Merdeka Curriculum in developing Arabic language competencies among secondary school students, specifically listening (istimāʿ), speaking (kalām), reading (qirāʾah), and writing (kitābah). This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. A systematic search was conducted across Google Scholar, DOAJ, Scopus, and ResearchGate, resulting in 36 peer-reviewed articles published between 2015 and 2025 that met the inclusion criteria and were analyzed thematically. The findings indicate that KTSP predominantly supports receptive and structural competencies, particularly reading and grammatical mastery, but provides limited opportunities for oral skill development. The 2013 Curriculum demonstrates more systematic literacy development through a scientific approach, although listening and speaking skills remain uneven due to variations in resources and teacher readiness. Meanwhile, the Merdeka Curriculum shows relative effectiveness in integrating receptive and productive skills through differentiated and project-based learning, although its implementation outcomes vary across educational contexts. This review contributes original insight by offering a comprehensive comparative synthesis of three national curricula and highlighting that curriculum effectiveness is shaped not by structural reform alone, but by pedagogical alignment, institutional readiness, and contextual support in Arabic language education. This article is also available at gb777